Detección de estado de ansiedad o estrés situcional a partir de parámetros no linguisticos de la voz. (2018)
A study was carried out on the effects of stress in a given situation on the characteristics of the voice signal, for this purpose a data processing was carried out using machine learning classification tools or machine learning.